Light and Electron Microscopic Observations in Nerve Cell Nucleolar Damage in Human Traumatic and Complicated Brain Injuries - Castejón, Orlando (Revista de la Universidad del Zulia)
Objective: To study microscopically the nucleolar alterations induced by severe and complicated traumatic human head injuries using cortical biopsies taken during neurosurgical treatment. Material and methods: 10 cortical biopsies from different cortical regions were study by means of light microscopy, scanning-transmission electron microscopy, and transmission electron microscopy. Results: Pyramidal nerve cells examined with light microscopy thick sections, and scanning-transmission electron microscopy semithin sections exhibited apparent intact nucleolar structure, and ring-shaped nucleolar morphology. Ultrathin sections examined by transmission electron microscopy showed some populations of edematous non-pyramidal neurons exhibiting normal nucleolar substructure with well preserved subcompartments. Another groups of non-pyramidal neurons displayed a nucleolar homogenization process without distinction of nucleolar subcompartments. Other neuronal populations and perivascular astrocytes showed a frank nu- cleolar disassembly process. The nucleolar morphological alterations are discussed in relation with the traumatic brain injury, anoxic ischemic conditions of brain parenchyma, oxidative stress, calcium overload, glutamate and hemoglobin excitotoxicity, and caspase activation. Conclusion: The complicated traumatic brain injuries showed neuronal populations with apparent intact nucleolar structures, and other neuronal groups with homogenization, disassembly and fragmentation of nucleolar components.